Studi Tentang Pengelolaan Obyek Wisata Pantai Cicalobak di Kecamatan Mekarmukti Kabupaten Garut - Erna Rustiana; Muchtar Muchtar; Nisa Fitriani (Jurnal Pembangunan dan Kebijakan Publik, 2019)
This research is based on the weakness of Human Resources in managing the tourism especially Cicalobak Beach in Kecamatan Mekarmukti Garut Regency. Tourism industry in Indonesia should get special attention from the government, both central and local government in developing tourism potential. The development of the tourism industry itself has a strong influence for the development of the region in the area around the tourism object, because it can act as the main sector industry, namely the superior sector that can improve the regional economy. Therefore, this research is focused on the management of tourism object especially in Cicalobak Beach. The management of tourism object in Cicalobak Beach uses G.R Terry (2011:10) theory which is management planning theory or often referred to as POAC stands for Planning, Organizing, Actuating, and Controlling. This study aims to find out how the study of the management of attractions in Cicalobak Beach District Mekarmukti Garut regency. Research uses qualitative methods. The author took the research location at Cicalobak Beach and Village Office Karangwangi District Mekarmukti Garut, involving Village Government and community Karangwangi Village District Mekarmukti Garut with the number of informants 6 people. From the results of interviews and observations, it was found that the management in Cicalobak Beach is still lacking in terms of Human Resources and has not been optimal because this beach is opened as a new tourist attraction around 2012. So it still requires good management to promote the tourism object.